Thermoeconomic optimization for irreversible absorption refrigerators and heat pumps - Kodal, A; Sahin, B; Ekmekci, I; Yilmaz, T (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
A performance analysis using finite time thermodynamic based on a thermoeconomic objective function has been performed for absorption irreversible refrigerators and heat pumps. The optimal design parameters at the maxima of the thermoeconomic objective functions for an absorption refrigerator and heat pump have been derived analytically, and the effects of the internal irreversibility, the economical parameter and the external temperatures on the global and optimal performances have been discussed. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: absorption refrigerator; absorption heat pump; finite time thermodynamics; thermoeconomic optimization; OPTIMAL PERFORMANCE-CHARACTERISTICS; DRIVEN; SYSTEM; COLLECTOR; ENGINE; CYCLE; Thermodynamics; Energy & Fuels; Mechanics